2018
DOI: 10.1080/09658211.2018.1434800
|View full text |Cite
|
Sign up to set email alerts
|

Remembering the past and imagining the future: attachment effects on production of episodic details in close relationships

Abstract: Attachment theories and studies have shown that Internal Working Models (IWMs) can impact autobiographical memory and future-oriented information processing relevant to close relationships. According to the constructive episodic simulation hypothesis (CESH), both remembering the past and imagining the future rely on episodic memory. We hypothesised that one way IWMs may bridge past experiences and future adaptations is via episodic memory. The present study investigated the association between attachment and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Expectancies about social interactions are partly situation-specific 46 ; however, there is a component of them that is influenced by individuals' temperament and stable working models (schemas) of self and others 47 . The LODESTARS was designed to tap the stable component, by probing participants’ expectancies for interactions with peers (with whom the participant is motivated to interact) in a generic social event context.…”
Section: Methodsmentioning
confidence: 99%
“…Expectancies about social interactions are partly situation-specific 46 ; however, there is a component of them that is influenced by individuals' temperament and stable working models (schemas) of self and others 47 . The LODESTARS was designed to tap the stable component, by probing participants’ expectancies for interactions with peers (with whom the participant is motivated to interact) in a generic social event context.…”
Section: Methodsmentioning
confidence: 99%
“…Episodic memory and simulation are flexible, can be reconstructed, and have diverse adaptive functions, such as benefiting planning, problem-solving, and various goal-directing behaviors (Schacter, 2012). Previous research has indicated that one way for IWMs to connect past experience and future adaptation is through episodic memory (Cao et al, 2018). These characteristics are very consistent with Bowlby’s notion about IWMs, as Bowlby (1988) emphasized the “working” aspect of mental attachment models to reflect the idea that these representations are not static and can be manipulated to find optimal solutions to specific problems.…”
Section: Discussionmentioning
confidence: 99%
“…Autobiographical memory and simulation task. We selected six picture cues (size, 964 Â 734 pixels) from a prior study (Cao, Madore, Wang, & Schacter, 2018), each depicting a scenario with high familiarity and imaginability for young college students. Pictures were presented on a computer screen with the relevant instructions.…”
Section: Qrimentioning
confidence: 99%
“…1 Expectancies about social interactions are partly situation-specific; 74 however, there is a component of them that is influenced by individuals' temperament and stable working models (schemas) of self and others. 75,76 The LODESTARS was designed to tap the stable component, by probing participants' expectancies for interactions with peers (with whom the participant is motivated to interact) in a generic social event context. The scenario described in the LODESTARS is emotionally ambiguous, and thus in line with existing measures in which participants imagine themselves in an emotionally ambiguous (future) scenario.…”
Section: Measuring Dispositional Social Expectancies: the Lodestarsmentioning
confidence: 99%